The Effectiveness of the Shadow Lamp Badminton Model as a Footwork and Stroke Training Athlete for PBSI Badminton Athletes in Merauke - Arifin Ika Nugroho,; Lay Riwu,; Hendra J Hiskya,; Ronald,; Sugeng Purwanto,; Widiyanto, (Technium Social Sciences Journal, 2023)
Based on the problems that occur in badminton athletes for Merauke Regency PBSI, namely the difficulty for athletes to master badminton footwork and stroke movements due to the lack of badminton training facilities and infrastructure owned by PBSI Branch Merauke, so there is a need for a solution to overcome these problems. This research has the meaning: Knowing the effect of the Shadow Lamp Badminton Model as a Footwork and Stroke Training Tool for PBSI Merauke Badminton Athletes. The method in this research uses an experimental method in the form of a Quasi Experiment, namely the Non Randomized Control Group Pretest-Posttest Design. The subjects of this study were 14 PBSI Badminton Athletes in Merauke Regency, with male and female gender criteria. this research will find out the difference in these levels of ability of athletes in using the application of electronic knowledge in badminton sports to help athletes practice footwork and badminton strokes through shadow lamps and using conventional models. The instrument to measure the ability of footwork and stroke is the foot circuit test. the results of this research namely, footwork and stroke skills increased. get a significance result of 0.000 <0.05. This Badminton Model Shadow Lamp is effective as a Footwork and Stroke Training Tool for PBSI Merauke Badminton Athletes.